2020
DOI: 10.3390/su12197919
|View full text |Cite
|
Sign up to set email alerts
|

Embedded Information Problem-Solving Instruction to Foster Learning from Digital Sources: Longitudinal Effects on Task Performance

Abstract: This research paper is based on a longitudinal study to find out how long-term embedded whole-task instruction can help students to develop more efficient information problem-solving (IPS) skills that could lead to a better use of internet information for learning and solving digital tasks more effectively. To this end, we designed, implemented and evaluated a three-year instruction programme to promote students’ development of key IPS skills in real-life classroom settings. This research involved sixty-one se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
(159 reference statements)
1
1
0
Order By: Relevance
“…I should admit that I have forgotten the purpose of drawing. (PALD 5) This finding is in line with the earlier research in a student-student collaborative learning context, which found adaptive assessment in collaborative learning leads to an improved understanding of task objective and achievement in task process during the collaborative learning process, which in turn positively influence the task performance (Pifarré & Argelagós, 2020).…”
Section: The Effects Of Sac On Public Utility In Effectivenesssupporting
confidence: 84%
“…I should admit that I have forgotten the purpose of drawing. (PALD 5) This finding is in line with the earlier research in a student-student collaborative learning context, which found adaptive assessment in collaborative learning leads to an improved understanding of task objective and achievement in task process during the collaborative learning process, which in turn positively influence the task performance (Pifarré & Argelagós, 2020).…”
Section: The Effects Of Sac On Public Utility In Effectivenesssupporting
confidence: 84%
“…Most widely used instruments are (1) think-aloud protocols, that consists of registering the utterances that the user is verbalising while solving a task (Ericsson and Simon, 1993), (2) retrospective reporting, in which participants report the thoughts while they are working on a task immediately after task performance (Van Gog, Paas, Van Merriënboer, and Witte, 2005), and (3) cued-retrospective reporting, in which participants are prompted with recordings of their task performance including recordings of their actions and eye movements (Hansen, 1991), and therefore the task performance is not influenced by the fact of verbalising their thoughts at the same time (Schmeck, Opfermann, Van Gog, Paas,and Leutner, 2015;Schwonke, Berthold and Renkl, 2009). Concerning product assessment, the task performance can be analysed through: (1) answer forms, that are the answers given by the users while solving the task, which are collected or registered in order to apply a qualitative or quantitative analysis (e.g., Pifarré and Argelagós, 2020;Somerville et al, 2008;Walhout, Oomen, Jarodzka and Brand-Gruwel, 2017). And (2) portfolios, that are able to collect, store, and create working products in different formats as a result of the learning process of acquiring Figure 1.…”
Section: Information Problem-solving Skills Assessmentmentioning
confidence: 99%